Efeitos da glibenclamida sobre a ativação cardíaca de inflamassoma NLRP3 induzida por dieta rica em carboidratos refinados - Renata Gomes Miranda e Castor (2019)
The consumption of foods with high refined sugars has been increasing in recent years. The discussion of sugar as the main deleterious macronutrient to the cardiovascular system, rather than salt and saturated fat, gained notoriety. A prospective study in 18 countries showed that carbohydrate consumption greater than 60% of daily energy is associated with a high risk for heart disease and mortality. Sugar is a known activator of pancreatic cell injury by the activation of NLRP3 inflammasome. NLPR3 inflammasome is a protein complex formed by the NLRP3 receptor, an adapter protein named ASC, and caspase-1, which culminates in the maturation of pro-inflammatory cytokines such IL-1β and IL-18. However, it has not been demonstrated yet whether this mechanism is also involved in the cardiac injury induced by the HC diet. The objective was to elucidate the mechanism involved in the development of cardiac damage induced by the HC diet, by pharmacological inhibition of NLRP inflammasome with a low dose of glibenclamide. Male Balb/c mice were fed with chow or HC diet for eight weeks. Glibenclamide (20mg/kg, i.g.), a sulfonylurea that inhibits NLRP3 inflammasome or vehicle were given daily in the final four weeks. The animals had free access to water and food and were divided into four groups: control-vehicle (CV), control-glibenclamide (CG), HC-vehicle (HCV), HC-glibenclamide (HCG). Noninvasive blood pressure measure and insulin resistance test (IRT) were performed before and after the treatment. All animals were euthanized by decapitation under anesthesia (ketamine: xylazine, 80:10 mg/kg, I.P.); the heart and other organs, and adipose tissues were harvested and weighed. The HC diet caused morphofunctional damage to the heart. There was an increase in the heart weight heart and left ventricle thickness and a decrease in the left ventricular chamber area, indicating concentric cardiac hypertrophy. The HC diet also caused an impairment in heart contraction and relaxation, with no change in blood pressure. Importantly, there was an increased in caspase-1 activity in situ. All heart changes induced by the HC diet were reversed by glibenclamide without interfering with IRT. We conclude that the consumption of a diet rich in refined carbohydrates causes damage to the heart through the activation of NLRP3 inflammasome and, consecutively, increased caspase-1 activity. Glibenclamide reverses the remodeling and cardiac dysfunction caused by the HC diet, being a promising drug to prevent the development of heart failure.